SimCCS: An open-source tool for optimizing CO2 capture, transport, and storage infrastructure. (February 2020) - Middleton, Richard S.; Yaw, Sean P.; Hoover, Brendan A.; Ellett, Kevin M.
Abstract: Commercial-scale carbon capture and storage (CCS) technology will involve deploying infrastructure on a massive and costly scale. This effort will require careful and comprehensive planning to ensure that capture locations, storage sites, and the dedicated CO2 distribution pipelines are selected in a robust and cost-effective manner. Introduced in 2009, SimCCS is an optimization model for integrated system design that enables researchers, stakeholders, and policy makers to design CCS infrastructure networks. SimCCS 2.0 is a complete, ground-up redesign that is now a portable software package, useable and shareable by the CCS research, industrial, policy, and public communities. SimCCS 2.0 integrates multiple new capabilities including a refined optimization model, novel candidate network generation techniques, and optional integration with high-performance computing platforms. Accessing user-provided CO2 source, sink, and transportation data, SimCCS 2.0 creates candidate transportation routes and formalizes an optimization problem that determines the most cost-effective CCS system design. This optimization problem is then solved either through a high-performance computing interface, or through third-party software on a local desktop computing platform. Finally, SimCCS 2.0 employs an open-access geographic information system framework to enable analysis and visualization capabilities. SimCCS 2.0 is written in Java and is publicly available via GitHub to encourage collaboration, modification, and community development. Highlights: Carbon capture and storage (CCS) is a critical climate mitigation technology. CCS infrastructure has to be cost-effectively deployed at a massive scale. CCS includes optimizing capture locations, storage sites, and the CO2 pipelines. SimCCS 2.0 is a new CCS software package for research, industry, and policymakers.